Management of heterogeneous iot devices over unite abstraction on gateways - Stepko, A. (ХНУРЕ, 2019)
IoT devices differ in their structure and interaction interfaces. This heterogeneity of IoT devices in Smart House management systems increases the complexity of such systems and make them hard to use. Introducing of abstraction for devices will allow to enclose devices heterogeneity details in some Gateway devices and hide for higher levels of the system